Determinant of Purchase Decision of Halal Cosmetics Among Generation Z - Norvadewi; Fitria Rahmah; Indah Hermayulia (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Halal living trends gave birth to innovation and revolution in the cosmetic industry with the advent of halal cosmetic products. Halal cosmetics are considered capable of meeting the needs of Muslim consumers. However, the Muslim community, especially generation Z, is increasing awareness of halal cosmetics. Therefore, halal cosmetics must compete with various other cosmetic brands. This study reveals the factors influencing purchasing halal cosmetics among generation Z in Samarinda city. This research is a quantitative study. Data collection techniques use questionnaires and documentation—the questionnaire was distributed to 234 samples selected by purposive sampling. Data analysis techniques use multiple regression analysis. The results showed that halal labels had no significant effect on purchasing decisions. In contrast, the price and quality of products significantly affected halal cosmetic purchase decisions in generation Z of Samarinda city. Simultaneously, halal labels, price, and product quality significantly affect the purchasing of halal cosmetics in generation Z of Samarinda city because the significance level is 0,000 < 0.05 or F count 149,066 > F table 3.01. The magnitude of the determination coefficient value is 0.660, meaning that the influence of independent variables on dependent variables is 66%. The remaining 34% is determined by other variables not studied.